Field delineation of geomorphic process domains along river networks in the Colorado Front Range - Livers, Bridget, author; Wohl, Ellen, advisor; Rathburn, Sara, committee member; Bledsoe, Brian, committee member (Colorado State University. Libraries, 2013)
Many of the conceptual models developed for river networks emphasize progressive downstream trends in morphology and processes. Such models are well-suited for larger, low-gradient rivers, but fall short in describing the extreme variability associated with headwater streams, which occupy the majority of length of stream networks, provide unique biological productivity and habitat, and can be sites of great sediment production. A more thorough understanding of the influence of local variability of process and form in headwater stream channels is required to remotely and accurately predict channel geometry characteristics for management purposes. Local variability of valley types and sediment production, or local process domains defined as glacial versus non-glacial valleys and levels of valley confinement, was evaluated for the Colorado Front Range by systematically following stream channels, categorizing them into stream type and process domain, and evaluating a number of channel geometry characteristics. The 111 reaches were then evaluated for significant differences in channel geometry among stream types and process domains, location and clustering of stream types on a slope-drainage area (S-A) plot, and downstream hydraulic geometry relationships. Statistical analyses revealed significant correlations between channel type and channel gradient, and channel type and substrate size. Although downstream hydraulic geometry relationships are well-defined using all reaches in the study area, reaches in glacial valleys display much more variability in channel geometry characteristics than reaches in fluvial valleys, as evidenced in larger ranges of channel geometry characteristics, greater difficulty in efficiently classifying stream types, less pronounced downstream hydraulic geometry relationships, and greater scatter of reaches on an S-A plot. Streams flowing through inherited terrain in glacial valleys continue to adjust to sediment and water dynamics, and level of confinement influences locations of certain stream types. Thus, local spatial variability associated with process domains at the reach scale (101-102 m) overrides progressive downstream relationships in mountain headwaters, and field calibration of relations between reach-scale channel gradient and channel characteristics is necessary to predict process and form of headwater streams in the Colorado Front Range.
Keywords: Colorado Front Range; process domains; fluvial geomorphology